Rural decline and policing of cannabis legalisation in Washington - Stanton, Duane L. (Policing and society, 2022)
Cannabis legalisation was viewed with great concern by law enforcement personnel. Here we show that police perceptions of the societal effects of legalisation are shaped to a considerable degree by officers’ geographic context. Urban communities tend to be relatively prosperous and hold political and social views characterised as progressive. In contrast, rural areas tend to be much less affluent, and their residents tend to share relatively conservative political and social views. Often lacking in resources, rural police agencies experience greater difficulty with the implementation of a broad new social policy such as cannabis legalisation. We investigate how the rural or urban and east/west geographic locus of a police officer tends to shape their perceptions on cannabis-related issues. Our qualitative study involved interviews conducted in 2018 and 2019 of 67 officers from 24 agencies across Washington. Officers were drawn from 11 urban, 1 rural, and 2 tribal police departments in western Washington, and 5 urban and 3 rural police departments in eastern Washington. Both common concerns and some differing perceptions were articulated by these officers from urban and rural agencies. The common circumstance of rural decline is present in Washington as elsewhere in the US; the findings reported here suggest that marijuana legalisation outcomes will likely entail greater challenges of adaptive implementation in rural areas experiencing decline than in urban centres in those states currently reforming their marijuana laws.